A Study on Chinese Speaking Anxiety and Chinese Speaking Learning Strategies among Thai Chinese Language Learners - Suttiphan, Nujaree; Srisinthon, Pairin (Journal of Education Culture and Society, 2025)
Aim. This research aims to investigate the factors affecting anxiety in speaking Chinese, the level of anxiety and the use of strategies in speaking Chinese, and the relationship between anxiety and the use of strategy in speaking Chinese among Thai Chinese Language Learners. Methods. This mixed-methods study investigates 155 Thai Chinese language learners using a questionnaire on speaking anxiety, strategies, and interviews. Results. The findings reveal that test anxiety is the most significant factor influencing learners’ overall anxiety. A correlation was found between speaking anxiety levels and strategy use: learners with low anxiety tended to employ affective and social strategies, while those with high anxiety relied more on compensation strategies. Additionally, a statistically significant negative correlation (p < 0.01) was observed between speaking anxiety and the use of speaking strategies. Conclusions. Speaking anxiety and the use of inappropriate speaking strategies significantly affect the development of language skills among Thai Chinese Language Learners. To address these issues, teachers should adopt the role of a speaking consultant by providing tailored guidance on selecting speaking strategies that align with learners’ individual characteristics. Creating a friendly and non-threatening classroom atmosphere is crucial to reducing anxiety. Furthermore, allowing sufficient preparation time before speaking assessments and providing regular opportunities for conversational practice can help build learners’ confidence in communication and foster sustainable motivation for learning Chinese. Cognitive value. These findings can serve as valuable input for developing curricula and teaching methodologies tailored to enhance Chinese speaking skills among Thai learners.